Insinuation in the View Talk Show: A Cognitive Discourse Analysis - Kareem, Hussein Hamid; Kadhim , Sadiq Mahdi (Journal of Ecohumanism, 2024)
This study is about the insinuation in the View talk show from the cognitive discourse perspective. It aims to show how lack of knowledge can affect the way people talk to each other. This is conducted by the aid of an eclectic model of Johnson’s Conceptual Metaphor (1980), and Sharfian’s Cultural Cognition ( 2011 ). The data is collected from the episodes on You Tube from an American talk show called the View. It is concluded that insinuation is a process of indirect communication that is done according to some strategies for many purposes, among them is to avoid social embarrassment.